Análise da resistência à fadiga e resistência à corrosão em instrumentos Hyflex EDM, Hyflex CM e Race - Paula Ribeiro Garcia (2021)
The aim of this study was to assess the fatigue and corrosion resistance of NiTi endodontic instruments. HyFlex EDM 25 /. ~, HyFlex CM 30/.06 and RaCe 30/.06 were used. Chemical composition was determined by energy-dispersive X-ray spectroscopy, phase constitution by X-ray diffraction and transformation temperatures by differential scanning calorimetry. Surface roughness was analyzed by atomic microscopic force (AFM) and the geometric characterization of the instruments was performed by measuring the diameter at 3mm from the tip. Initially, 10 instruments from each group were tested until rupture in the flexural fatigue bench to obtain the mean time until fracture. Then, new instruments were subdivided into control and experimental groups for each system. Experimental groups were subjected to fatigue tests, up to ¾ of the mean time to rupture and subsequently to corrosion tests. Control groups were directly subjected to the same corrosion tests. Weibull analysis was applied to assess the reliability in the tested instruments to failure. Analysis of variance with a significance of 0.05% was adopted for the results of chemical composition, phase transformation temperature, diameter, roughness, and corrosion tests. The chemical composition was near equiatomic in RaCe instruments, with the presence of Nickel and Titanium. On the other hand, EDM and CM instruments presented, in addition to these elements, Oxygen in the composition. The structural characterization showed higher Af phase transformation temperatures (austenite finish) for the heat treated groups (CM and EDM), this data was confirmed by the results of X-ray diffractometry with the presence of R-phase and austenite (phase β) at room temperature for both. The RC group had lower temperatures Af (p<.05), in addition to only austenite in the XRD analysis. Diameter measurements showed no statistically significant differences between the CM and RC groups, both significantly larger than EDM. Flexural fatigue tests showed time to fracture with no difference between EDM and CM (p>0.05) and both were superior to RC (p<0.05). However, the Weibull analysis showed better reliability parameters for RC and CM. The corrosion tests showed significant differences between the analyzed systems, but not between new and cycled instruments. The CM groups showed greater resistance to corrosion, followed by EDM and RC. Surface roughness was higher in CM instruments, followed by EDM and RC. According to the results, the microstructure of the thermally treated instruments improves fatigue resistance and corrosion resistance, regardless of the type of machining